Mixed Method Evaluation of a Graduate Student Teaching and Learning Internship Program - Tavener, Meredith; Majeed, Tazeen; Bagade, Tanmay; Weaver, Natasha; Reeves, Penny; Dsilva, Shefi; James, Erica L. (Frontiers in Public Health, 2021)
In recognition of the need to better prepare doctoral candidates with teaching and learning competencies, we devised an innovative internship program in the form of a structured apprenticeship and triailled it in public health higher education. The paid internship was comprised of: i) Mentoring from an experienced educator, ii) Structured program of education in pedagogy and curriculum design, and iii) Opportunities for applied experience. Eleven interns completed the apprenticeship in its first two years. The mixed method evaluation assessed the impact of the internship on knowledge, skills, and confidence of interns throughout the internship, and included a cost-consequence analysis. Data collection included surveys and face-to-face interviews with interns and mentors. Changes in intern knowledge and skills were analysed by intern self-ratings pre- and post-internship on 11 performance descriptors. All interns indicated improvement in at least one area of teaching. Interviews indicated general satisfaction, however raised incompatibilities between the unstructured nature of mentoring and intern expectations and preferences. The economic analysis calculated a cost-offset associated with intern-delivered teaching activities of $58,820 (AUD, 2019). The total cost of the program was calculated to be $70,561 (comprising mentor investment AUD$20,436, intern investment AUD$15,126, scholarship ‘top-up’ payment of $5000 paid to each of the 7 interns AUD $35,000). This Internship is associated with positive impacts for interns across a range of domains at a net total investment of $11,741.